Winter resource selection by the American marten (Martes americana): the effect of model resolution - McKague, Curtis Ian (University of Guelph, 2007)
Successful management requires an understanding of the scale at which species use resources within their environment. Research shows considerable variability in resource preferences of American martens ('Mantes americana ') across North America. This variability may be an artefact of the resolution used in analyzing resource selection. To test the effects of resolution, winter resource selection of martens was evaluated using resource-based models at coarse (i.e., forest stands) and fine (i.e., local sites within forest stands) resolutions near Kapuskasing, Ontario. None of the predictor variables reliably explained resource use by martens at the coarse resolution. Fine-resolution models, however, suggested that martens selected sites with a greater abundance of coarse woody debris and a greater proportion of cedar trees in comparison with available sites within marten home ranges. On average, fine-resolution models performed ten times better than coarse-resolution models in classifying resource use by martens.